PREDATION BY YOUNG Cassis tuberosa LINNAEUS, 1758 (MOLLUSCA: GASTROPODA) ON Mellita quinquiesperforata (CLARCK, 1940) (ECHINODERMATA:ECHINOIDEA), UNDER LABORATORY CONDITIONS - Pequeno, Ana Paula Leite Cavalcante; Matthews-Cascon, Helena (Arquivos de Ciências do Mar, 2017)
In Icapuí County, Ceará State, Northeast Brazil, young individuals of Cassis tuberosa Linnaeus, 1758 are frequently found feeding on Mellita quinquiesperforata (Clarck, 1940). In this study we analyze the predatory behavior of young C. tuberosa on the sand dollar M.quinquiesperforata. Individuals of predator and prey were collected at low tide and were taken to the laboratory in aerated boxes. Each Cassis tuberosa was placed together with 20 adult individuals of Mellita quinquiesperforata in 60-liter tanks. During the experiment the number of consumed prey was registered and the eaten individuals were replaced. This experiment lasted for one month at 28ºC and was replicated five times. We registered the position and the dimensions of the bore holes on the sand dollars. The bore holes were complete, with 4 to 5 mm of diameter and had teeth marks of the radulae on their edge. We found, in every prey, a dark spot around the predation holes, which was probably a reaction of the calcium carbonate shell of the prey to the sulfuric acid from the predator. Statistically-significant preference for oral or aboral sides was not observed, but most predation by C. tuberosa on Mellita quinqiesperforata was on the oral surface and close to the mouth. The defense mechanism of the prey was based on behavioral strategies.